Rickettsiae of the spotted fever group in Hungary - Rehácek, J; Nosek, J; Urvölgyi, J; Sztankay, M (Folia parasitologica, 1979)
Rickettsiae were detected by haemocyte test in 7.2% of Dermacentor marginatus and 4.7% of D. reticulatus ticks collected in Hungary. Six strains of rickettsiae were isolated from positive specimens. These rickettsiae according to CFR are closely related, probably identical with R. slovaca and they represent the first rickettsiae of the Spotted Fever group found in that country.
Keywords: Hungary; Rickettsia; klíšťata; Ticks; Maďarsko; Dermacentor